Power generation technologies - Breeze, Paul A. (Newnes, 2005)
Paul Breeze provides a concise and readable description of the spectrum of different power generation technologies available today, from traditional fossil fuels and the better established renewables such as wind and solar power, to emerging renewable such as biomass and geothermal energy. Technology solutions such as combined heat and power, and distributed generation are also explored. However, this book is more than just an account of the technologies - for each method the author explores the economic and environmental costs and risk factors. Those involved in planning and.